MAKING OF MATCHING GAME BOOK TO LEARN ENGLISH VOCABULARY - Jusnaini Jusnaini; Aswandi Aswandi (Politeknik Negeri Bengkalis, 2016)
Abstract : Learning English is very important in this competitive world. It shows that we have to master English. However, in learning it, the learners still feel bored and face difficulties. For example, in learning Vocabulary, they always have problems in memorizing the words. Therefore, the use of learning media can be more effective and interesting way in learning. The main purpose of this final project is to make a matching game book which can be used as an alternative learning medium in learning Vocabulary, especially, for students in lower education level. The idea of this project is based on the real concept, the students actually still feel bored in learning English. This project results a set of matching game book consists of a game book, a sets of picture cards and a set of word cards. This game can be used in classes during learning-teaching process to help the students to memorize the word. By using this game, the student can learn vocabulary in a more interesting and effective way.Keywords: Matching Game Book, picture cards, word cards.